Literasi Anti Korupsi Bersama Generasi Muda, Wujudkan Indonesia Bebas Korupsi - Louisa Anwar Hasibuan; Anis Soraya; Firdaus Firdaus; Mutiara Hamda; Nayla Zafira Indra; Nabil Hukama Zulhaiba; Dinda Aulia; Dominick Hoki Pinky; Lidya Andita; Ricy Hilmayandani (Jurnal Pendidikan dan Kewarganegara Indonesia, 2025)
Corruption is one of the biggest problems facing Indonesia. Education plays an important role in building the character of the younger generation with integrity and anti-corruption. This research aims to identify the effectiveness of anti-corruption literacy in forming a corruption-free character of the younger generation at the Darel Hikmah Islamic Boarding School, which is one way to instill anti-corruption values ​​from an early age among students. Apart from that, this research also evaluates the application of a religion-based approach in tackling corrupt behavior and provides recommendations for developing similar programs in other Islamic boarding schools. The method used in this research is literature study, which involves a series of library data collection activities, reading, taking notes, and managing data objectively, systematically, analytically, and critically. The focus of this research is on The Power of Two learning model which aims to improve students' critical thinking skills at the Darel Hikmah Islamic Boarding School. The results of the research show that the anti-corruption literacy program implemented at the Darel Hikmah Pekanbaru Islamic Boarding School has proven to be quite effective in instilling the values ​​of integrity and honesty in its students. However, this research also identified challenges in implementing the program that require further attention. This shows the importance of continuous evaluation and development to ensure the success of the program in achieving the expected educational goals.